Inheritance of a ring 14 chromosome. Issue 3 (June 1981) - Riley, S B; Buckton, K E; Ratcliffe, S G; Syme, J
Abstract : A family is described in which the mother, her two live offspring, and a therapeutically aborted fetus each had a ring 14 chromosomes. The two children were mentally retarded and the mother's intelligence was at the lower end of the normal range. In addition, the mother had two spontaneous abortions, one of which was shown to be chromosomally normal.